2014
DOI: 10.1016/j.vetmic.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of Staphylococcus aureus colonization in pigs in Ireland

Abstract: 22The emergence of methicillin-resistant Staphylococcus aureus (MRSA) in livestock has 23 refocused attention on S. aureus colonization and transmission in pigs. This study 24 investigated the effect of the S. aureus colonization status of a sow on the colonization status 25 of her piglets, and whether pigs carry the same strain of S. aureus throughout production. 26 Nasal swabs were collected from the piglets of six healthy sows two days after birth and two 27 days before and two days after they were moved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
0
13
0
2
Order By: Relevance
“…The association between the MRSA status of the sow and the probability of piglets testing MRSA positive have been confirmed in several studies [ 45 47 ]. In our model, the probability of transmission from sow to new-born piglets was based on predictions from a study, where piglets had been sampled within one hour after birth and again after one day [ 47 ].…”
Section: Discussionmentioning
confidence: 80%
“…The association between the MRSA status of the sow and the probability of piglets testing MRSA positive have been confirmed in several studies [ 45 47 ]. In our model, the probability of transmission from sow to new-born piglets was based on predictions from a study, where piglets had been sampled within one hour after birth and again after one day [ 47 ].…”
Section: Discussionmentioning
confidence: 80%
“…A total of 89 S. aureus isolates were cultured from 1371 samples picked up from March 2014 to December 2017. The isolates were originated from pigs (25), cattle (6), goats (10), rabbits (16) and chicken (32). Four MRSA strains were identified from 3 pig samples and 1 chicken sample.…”
Section: Resultsmentioning
confidence: 99%
“…Dan M et al showed that a high isolation rate of S. aureus (46.0%) was obtained from cattle farms in Xinjiang Province, China [29]. A longitudinal study in Ireland indicated the average prevalence of S. aureus colonization in pigs varied between 26% and 73% [32]. The study [31] carried out in Chongqing indicated that the prevalence (46%) of goat-associated S. aureus was higher than isolation rate (11.4%) of S. aureus obtained from goats in our study.…”
Section: Discussionmentioning
confidence: 99%
“…são bactérias Gram positivas ubíquas, encontradas nos mais diversos sítios e hospedeiros, estão presentes tanto na microbiota animal quanto na microbiota de indivíduos saudáveis. 1,2 Apesar de serem constituintes naturais da microbiota humana, são causas comuns de infecções de pele e mucosas, sendo também responsáveis por um considerável número de infecções hospitalares com alto risco de sepse. 3,4 Somado a isso, Staphylococcus aureus é o principal representante dos microrganismos causadores de toxinfecções alimentares causadas pelo consumo de alimentos contaminados por bactérias e/ou toxinas por estas produzidas, sendo ainda um dos principais agentes causadores de mastite bovina no sul do Brasil.…”
Section: Introductionunclassified